2011
DOI: 10.1097/rhu.0b013e3182290dbf
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Carotid Intima-Media Thickness and the Activity of Rheumatoid Arthritis

Abstract: Values of cIMT were significantly greater in RA compared with control subjects. Features of RA, such as extra-articular manifestations, erosions, high inflammatory parameters, and long disease duration, even in the absence of traditional clinical CV risk factors, were associated with greater cIMT, suggesting an unfavorable CV risk profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 39 publications
5
19
2
Order By: Relevance
“…and stated that age, systolic blood pressure, tender joint count, and swollen joint count had significant correlations with patient's CIMT. Also the results reported by Targon´ska-Stepniak (22) are consistent with us who stated that in RA patients, CIMT correlated positively with a number of immunological and inflammatory parameters and also with amino-terminal pro-brain natriuretic peptide (NT-proBNP), age, and metabolic variables (serum cholesterol, creatinine, cystatin C). In multiple linear regression analysis, significant association was found between CIMT and NT-proBNP and age.…”
Section: Discussionsupporting
confidence: 87%
“…and stated that age, systolic blood pressure, tender joint count, and swollen joint count had significant correlations with patient's CIMT. Also the results reported by Targon´ska-Stepniak (22) are consistent with us who stated that in RA patients, CIMT correlated positively with a number of immunological and inflammatory parameters and also with amino-terminal pro-brain natriuretic peptide (NT-proBNP), age, and metabolic variables (serum cholesterol, creatinine, cystatin C). In multiple linear regression analysis, significant association was found between CIMT and NT-proBNP and age.…”
Section: Discussionsupporting
confidence: 87%
“…long disease duration, degenerations, high inflammatory parameters, and extra-articular manifestations). 28 However, in this study, carotid IMT values were not associated with disease severity in FM patients.…”
Section: Discussioncontrasting
confidence: 67%
“…CIMT is a strong indicator of early atherosclerosis and cardiovascular disease and is commonly used in rheumatological diseases to assess the risk of cardiovascular disease (23,24). In addition, CIMT values are associated with certain clinical parameters (such as lengthy disease duration, degenerations, high inflammatory parameters, and extra-articular symptoms) in diseases, such as rheumatoid arthritis (25). In the literature, studies have shown the presence of early atherosclerosis with increased CIMT values in ankylosing spondylitis, rheumatoid arthritis and Behçet's disease compared to a healthy population (26,27).…”
Section: Discussionmentioning
confidence: 99%